Optimalisasi Hasil Belajar Siswa melalui Model Cooperative Learning Tipe Course Review Horay di Kelas V Sekolah Dasar - Salmi, Yuni; Reinita, Reinita (Universitas Negeri Padang, 2024)
This study aims to improve the learning outcomes of fifth-grade students of SDN 11 Campago Guguk Bulek Bukittinggi through the application of the Cooperative Learning method of the Course Review Horay (CRH) type. The problem faced is the less-than-optimal implementation of the independent curriculum by teachers, which affects the quality of learning. This study involved 21 students with a qualitative and quantitative approach in the form of classroom action research. Data collection techniques used observation, learning outcome tests with observation sheet instruments, interviews, and assessment rubrics. In contrast, data analysis used qualitative and quantitative analysis. The results of the study showed a significant increase in the quality of learning planning, teacher involvement, student participation, and learning achievement between cycles I and II. The average student learning achievement increased from 76.46 in cycle I to 91.84 in cycle II. These findings indicate that the application of the CRH method can improve students' understanding and learning achievement, and have a positive impact on the effectiveness of learning in the classroom.